Innovative Development and Economic Growth - YAGOLNITSER, Miron; PEREPETCHKO, Lyudmila; PEREPETCHKO, Lyudmila (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
With reliance on the World Bank statistics, we prove that innovation exports distribution is subjected to the well-known Zipf Law (rank – frequency distribution) – one of a family of related discrete power type probability distributions. For countries belonging to the core of high-tech exports power-type distribution, we define significant statistical dependences of the share of high-tech products being exported on the values pertaining to the innovative component of intellectual capital (patent applications, trademarks, pre-production prototypes and designs). We define a relation of the share of added value created in different countries to the share of their respective high-tech exports. We establish that under the current world economic crisis, the growth of innovation sector has multiplied the growth of added vale in an economy, with multiplication ratio > 1.